Incidentes de viaje espejo en Yucatán y otros lugares. - León de la Barra, Pablo; Arriola, Magalí (México : Instituto Nacional de Bellas Artes, 2011)
Wyn Evans, Cerith ; Catherwood, Frederick ; Charnay, Claude-Joseph Désiré ; Dixon y Augustus Le Plongeon, Alice ; Katz, Leandro ; Ortiz Torres, Rubén ; Castillo Deball, Mariana ; Santiago, Beatriz ; Hubbard, Alex ; Alias Editorial ; Millar, Jeremy ; Durant, Sam ; Sérandour, Yann ; Monk, Jonathan ; Escobedo, Helen ; Gori, Paolo ; Lake y Verea ; Untitled (Carl Andre Tropical) ; Gaillard, Cyprien ; Brüggemann, Stefan ; Brüggemann, Jürgen K. ; Almarcegui, Lara ; Garciá Torres, Mario ; López Landa, Mario ; Leguillon, Pierre ; Moore, Henry ; Goeritz, Mathias ; Tamayo, Rufino ; Piranesi, Giovanni Battista ; Maillé, Mauricio ; Orozco, Gabriel ; Rocha, Mauricio ; Hotel Palenque-Style Chairs ; Anonymous Tropical ; Fernández, Claudia ; Martin, Simon ; León de la Barra, Pablo
Incidents of Mirror-Travel in Yucatan and Elsewhere, Museo Tamayo, Mexico City, July 7th - August 7th, 2011
boek
Keywords: Mexico